SERUM PROTEINS AND BLOOD ALPHA AMINO NITROGEN IN CEREBRAL PALSY - Burman, David (1960)
The mean serum proteins of 30 children over the age of 3 suffering from cerebral palsy was 7.20 with a standard deviation of 0.49 g. per 100 ml. No difference was found between children with the spastic and athetoid types of cerebral palsy. The electrophoretic pattern of the serum proteins did not differ in the two types, but the alpha 2 globulin diminished significantly with increasing age. There was no difference that could be considered “clinically significant” between the total serum proteins or their electrophoretic pattern in children with cerebral palsy and in four published series of normal children. The plasma and whole blood alpha amino nitrogen showed no significant difference between the two types of cerebral palsy.